Floral development and embryology in the early-divergent grass Pharus - Sajo, M. G.; Longhi-Wagner, H.; Rudall, P. J. (Univ Chicago Press, 2007)
A detailed study of floral ontogeny, anatomy, and embryology in two (of six) species of Pharus is presented as part of a series of comparative investigations on early-divergent grasses. Pharus is a taxonomically isolated genus belonging to the earliest-diverging grass lineage with a true grass spikelet. It is unusual in possessing remarkably dimorphic florets: male florets possess two lodicules, six stamens, and a pistillode, whereas female florets lack lodicules entirely but possess six staminodes and a tricarpellary ovary with three stigmas. The rudimentary lodicules in male florets are initiated after the stamen whorls. There are most commonly six androecial organs, but in some florets, a five-staminate condition was observed, resulting from suppression of the abaxial stamen from the inner whorl, or even a four-staminate condition resulting from subsequent fusion of the two adaxial outer stamens (i.e., elements of both whorls). Thus, the pattern of floral zygomorphy in Pharus differs from that of many other grasses. Centrifixed anther attachment is reported for the first time in Pharus, resembling the condition in another early-divergent grass, Anomochloa, though anthers are introrse in Anomochloa compared with latrorse in Pharus. Anther wall development is of the reduced type in Pharus, in contrast to most other monocots. Microsporogenesis is of the successive type, as in many other monocots. The ovary develops from three distinct primordia and is unilocular with a single ovule and a pronounced ovary beak that is highly characteristic of Pharus. There is a hollow style, in contrast to the solid styles that are common in many other grasses. The embryo is highly differentiated, as in other grasses, with a distinct epiblast and a small cleft between the scutellum and the coleorhiza.
Keywords: grass floret; Poaceae; scutellum